Plasma protein biomarkers enhance the clinical prediction of kidney injury recovery in patients undergoing liver transplantation. Issue 6 (29th October 2014) - Levitsky, Josh; Baker, Talia B.; Jie, Chunfa; Ahya, Shubhada; Levin, Murray; Friedewald, John; Al‐Saden, Patrice; Salomon, Daniel R.; Abecassis, Michael M.
<x xml:space="preserve">Abstract</x> Biomarkers predictive of recovery from acute kidney injury (AKI) after liver transplantation (LT) could enhance decision algorithms regarding the need for liver‐kidney transplantation or renal sparing regimens. Multianalyte plasma/urine kidney injury protein panels were performed immediately before and 1 month post‐LT in an initial test group divided by reversible pre‐LT AKI (rAKI = post‐LT renal recovery) versus no AKI (nAKI). This was followed by a larger validation set that included an additional group: irreversible pre‐LT AKI (iAKI = no post‐LT renal recovery). In the test group (n = 16), six pre‐LT plasma (not urine) kidney injury proteins (osteopontin [OPN], neutrophil gelatinase‐associated lipocalin, cystatin C, trefoil factor 3, tissue inhibitor of metalloproteinase [TIMP]‐1, and β‐2‐microglobulin) were higher in rAKI versus nAKI (P < 0.05) and returned to normal values with renal recovery post‐LT. In the validation set (n = 46), a number of proteins were significantly higher in both rAKI and iAKI versus nAKI. However, only pre‐LT plasma OPN (P = 0.009) and TIMP‐1 (P = 0.019) levels were significantly higher in rAKI versus iAKI. Logistic regression modeling was used to correlate the probability of post‐LT rAKI, factoring in both pre‐LT protein markers and clinical variables. A combined model including elevated OPN and TIMP‐1 levels, age <57, and absence of diabetes had the highest area under the curve of 0.82, compared to protein‐only and clinical variable–only models. Conclusion: These data suggest that plasma protein profiles might improve the prediction of pre‐LT kidney injury recovery after LT. However, multicenter, prospective studies are needed to validate these findings and ultimately test the value of such protein panels in perioperative management and decision making. (Hepatology 2014;60:2016–2025)